Incidental finding of urinary schistosomiasis in a young adult: Radiologic features and a case report - Baba, Dr SULE Muhammad (Jour Med Resh and Health Sci, 2021)
Urinary schistosomiasis (US) is a burden in sub-Saharan Africa prevalently in Nigeria, and caused by a fluke called Schistosoma haematobium. This has a prevalence for the male gender and predominantly seen in children and adolescent. This is a 45-year-old farmer that was referred for pelvic radiograph and abdominal ultrasonography on account of recurrent right loin pain, dysuria and occasional terminal hematuria. The pelvic radiograph showed collapsed linear concentric rims of calcific densities in the region of the pelvic cavity centrally most likely a calcified, contracted and empty urinary bladder. The abdominal ultrasonogram demonstrated a urine distended urinary bladder with wall thickening of about 10mm more marked right laterally where a mucosal out-pouch and thickening of about 15.4mm was noted in its cranial aspect. There is associated right hydroureteronephrosis with enlarged right kidney, thinning of the cortical mantle and an echogenic focus in the lower calyceal moiety without acoustic shadow most likely a granuloma. An excretory pyelogram showed contrast excretion in both kidneys, moderate-severe dilatation of the right pevicalyces, dilated and tortuous contrast filled right ureter that had bulbous termination of part of the distal portion with non-demonstration of the remaining distal aspect most probably from fibrosis/stricture on account of schistosomiasis. The left collecting system and ureter were not dilated, though the distal left ureter appeared laterally deviated/curved simulating the left-lateral aspect of the so-called cow-horn appearance of schistosomiasis. A diagnosis of urinary schistosomiasis was made more marked on the right, the patient was placed on oral praziquantel with adequate monitoring and advice. We report a case of urinary schistosomiasis in a 45-year-old farmer, features of which were demonstrated following multiple imaging modalities.